Paleomagnetism of Jurassic carbonate rocks from Sardinia: No indication of post-Jurassic internal block rotations - Kirscher, Uwe; Aubele, K.; Muttoni, G.; Ronchi, A.; Bachtadse, V. (2011)
Several paleomagnetic studies on Carboniferous and Permian sedimentary and volcanic rocks from Sardinia and Corsica have recently demonstrated (1) the tectonic coherence between southern Corsica and northern Sardinia and (2) significant rotations between individual crustal blocks within Sardinia itself. The geodynamic significance of these rotations, however, is not clearly understood mainly because of uncertainties in defining their timing and causes. In order to contribute to these issues, a pioneering paleomagnetic study on Jurassic carbonates from the Baronie-Supramonte region of eastern-central Sardinia has been extended regionally and stratigraphically. A total of 280 oriented drill cores were taken from 44 sites of Middle and Late Jurassic age in the Nurra, Baronie-Supramonte, Barbagia-Sarcidano, and Sulcis regions. Despite generally weak remanent magnetization intensities, on the order of less than 1 mA/m, thermal and alternating field demagnetizations were successfully applied to define a characteristic remanent magnetization component in about 60% of the samples. Site mean directions show rather good agreement after correction for bedding tilt and yield Middle and Late Jurassic overall mean directions of D = 269.7° and I = 45.0° (α95 = 8.0°, k = 14, and n = 25 sites) and D = 275.5° and I = 50.7° (α95 = 7.2°, k = 45.3, and n = 10 sites). Positive regional and local fold and reversal tests demonstrate the primary character of the natural magnetic remanence, which is carried by magnetite. These results indicate only insignificant amounts (±10°) of post-Jurassic rotations within the island of Sardinia.The resulting Middle and Late Jurassic paleopoles (latitude (Lat) = 16.5°, longitude (Long) = 299.1°, dp = 6.4°, and dm = 10.1° and Lat = 23.4°, Long = 301.2°, dp = 6.5°, and dm = 9.7°), corrected for the opening of (1) the Liguro-Provençal Basin and (2) the Bay of Biscay using rotation parameters from the literature, fall near the coeval segment of the European apparent polar wander path. These results constrain the timing of large differential block rotations found in Late Carboniferous-Permian rocks to a pre–Middle Jurassic age and lead us to exclude tectonics related to the Alpine orogeny for such rotations.